Pelatihan Teknologi Pascapanen dan Pengolahan Kopi di Kabupaten Ponorogo - Tjahja Muhandri; Dian Herawati; Fahim Muchammad Taqi; Saraswati Saraswati; Ahmad Junaedi (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Coffee is one of the agricultural commodities in Ponorogo Regency that has high potential for development. Farmer’s limited knowledge of technology and innovation in post-harvest and coffee processing is an obstacle to improving coffee quality. This activity aims to train coffee farmers and coffee entrepreneurs in Ponorogo Regency to improve coffee quality and standards according to consumer specifications using new technologies and innovations. The training was conducted offline at the Sooko Subdistrict Office in Ponorogo Regency. There were 30 participants in the training. The activity was evaluated through tests at the beginning and end of the training to measure participants understanding during the training. A total of 10 questions in multiple choice form were given to participants. Data was collected from 23 participants. The average score of the participants increased from 3,9 to 5,9 (20% increased). The aspect that was difficult for participants to understand was related to coffee roasting.